PENGARUH KEMAMPUAN TEKNOLOGI DI ERA DIGITAL TERHADAP GAYA HIDUP PRAJURIT YON ARHANUD 3/ YUDHA BHUANA YAKCA - Purba, Endang Sri Kurniatun; Endang, Rini; Endang, Paulina Siregar (JURNAL DWIJA KUSUMA, 2025)
In order to create the influence of beneficial technological capabilities and to possess good technological capabilities, the role of a leader is essential. Therefore, the organization must develop soldiers who possess good technological skills and are beneficial in achieving goals, as the role of a leader is very important for an organization; without the role of an ideal leader, there will be no effort in achieving common goals. The Arhanud 3/YBY Battalion is one of the spearheads in maintaining the air security of the Republic of Indonesia, especially within the ranks of Kodam 3/Siliwangi, which requires a professional attitude and good technological capabilities to face technological advancements. This research aims to provide a positive influence to produce a positive impact on both the battalion and the members of the Arhanud 3/YBY Battalion in order to keep pace with future technological developments. The method used in this study is quantitative. In this study, the researcher obtained data through questionnaires, interviews with sources, observations, and document studies. The results of this study prove that the influence of technological capabilities has a more positive impact than the negative impact, this can be seen from the data from filling out questionnaires and from the results of in-depth interviews with informants, that the influence of technological capabilities is used for useful things, in order to achieve the goals that have been set in order to keep pace with technological developments in the upcoming digital era.